2008
DOI: 10.4049/jimmunol.181.10.7014
|View full text |Cite
|
Sign up to set email alerts
|

Thymocyte-Dendritic Cell Interactions near Sources of CCR7 Ligands in the Thymic Cortex

Abstract: Little is known about the dynamics of the interactions between thymocytes and other cell types, as well as the spatiotemporal distribution of thymocytes during positive selection in the microenvironment of the cortex. We used two-photon laser scanning microscopy of the mouse thymus to visualize thymocytes and dendritic cells (DCs) and to characterize their interactions in the cortex. We show that thymocytes make frequent contacts with DCs in the thymic cortex and that these associations increase when thymocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 44 publications
12
48
0
Order By: Relevance
“…Immature DN and DP thymocytes in the cortical region of mouse thymic slices migrated with speeds of approximately 4 μm/min, similar to previous reports for mouse cortical DN and polyclonal DP thymocytes from both intact and vibratome-cut thymic lobes (27,29,30). Mature human CD4 + and CD8 + SP thymocytes in the medulla migrated more rapidly than did immature cells in the cortex, exhibiting average speeds of approximately 9 and 12 μm/min, respectively ( Figure 2, A and B, and Supplemental Video 1; supplemental material available online with this article; doi:10.1172/ JCI67175DS1).…”
Section: Human Thymocyte Migration In Mouse and Human Thymic Environmsupporting
confidence: 68%
See 2 more Smart Citations
“…Immature DN and DP thymocytes in the cortical region of mouse thymic slices migrated with speeds of approximately 4 μm/min, similar to previous reports for mouse cortical DN and polyclonal DP thymocytes from both intact and vibratome-cut thymic lobes (27,29,30). Mature human CD4 + and CD8 + SP thymocytes in the medulla migrated more rapidly than did immature cells in the cortex, exhibiting average speeds of approximately 9 and 12 μm/min, respectively ( Figure 2, A and B, and Supplemental Video 1; supplemental material available online with this article; doi:10.1172/ JCI67175DS1).…”
Section: Human Thymocyte Migration In Mouse and Human Thymic Environmsupporting
confidence: 68%
“…In fact, as reported here and shown previously with mouse thymocytes (8,27,29), cortical thymocytes were more than 2-fold slower than their medullary counterparts. Moreover, we found that PTX treatment sharply reduced the speed of human SP thymocytes, but had a minor effect on DP thymocyte speed.…”
Section: Cxcr4 Signaling Retains Human Dp Thymocytes In the Thymic Cosupporting
confidence: 64%
See 1 more Smart Citation
“…We previously reported that steady-state cortical thymocytes expressing positive-selecting TCR transgenes migrate more rapidly than thymocytes bearing nonselecting or polyclonal TCRs (22,23). To resolve how the kinetics of migration evolves over time during positive selection, we examined thymocyte migration by two-photon microscopy at various times after introducing preselection DP thymocytes onto positiveselecting slices.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic studies have shown that medullary thymic DCs are nonmotile (19) and exhibit stable bodies while extending their dendrites (13). However, to date, information on thymic DC localization regarding TSCs as well as on DC/TSC dynamic interactions is lacking.…”
Section: Dynamic Interactions Of Dcs With Tscsmentioning
confidence: 99%